Impact of GABA and nutritional supplements on neurochemical biomarkers in autism: a PPA rodent model study - Alabdali, Altaf N.; Ben Bacha, Abir; Alonazi, Mona; Abuaish, Sameera; Almotairi, Ahmad; Al-Ayadhi, Laila; El-Ansary, Afaf K. (Frontiers in Molecular Neuroscience, 2025)
Background/objectivesAutism spectrum disorder (ASD) is associated with excitatory-inhibitory imbalance and oxidative stress. GABA, an inhibitory neurotransmitter, and related nutritional therapies are promising in restoring these imbalances. GABAergic deficits and glutamate excitotoxicity are two essential signaling pathways that could be addressed to treat autism, thus medications targeting these pathways are critical for treating behavioral symptoms. In a rat model of autism produced by propionic acid (PPA), this study assessed the effects of GABA supplementation and combined nutritional therapy (probiotics, vitamin D3) and β-lactam as an activator of glutamate transporter.MethodsSixty rats were randomly assigned into six groups: Group I (Control), Group II (PPA-treated), Group III (Control-GABA), Group IV (Control-Combination), Group V (PPA-GABA), and Group VI (PPA-Combination). Social behavior was evaluated using the three-chamber test. Selected biochemical variables related to oxidative stress (GST, Catalase, Lipid peroxides, GSH and Vitamin C), GABA and glutamate signaling (EAAT2, KCC2, NKCC1, GABA, VD3, Glutamate and GABRA5) were measured in the brain homogenates of the six groups. The hippocampus was examined histopathologically to assess cellular integrity.ResultsThe obtained data revealed that PPA treatment caused significant oxidative stress and neurotransmitter imbalances, characterized by reduced GABA and elevated glutamate levels. GABA supplementation alone produced moderate benefits in biochemical and behavioral markers, but combined therapy considerably restored GABA levels, reduced oxidative stress, and enhanced social interaction behaviors. Histopathology revealed that combination therapy mitigated neurodegenerative changes induced by PPA, preserving hippocampal cellular structure.ConclusionThis study demonstrated that combined therapy (GABA, probiotics, vitamin D3, and β-lactam) were more effective than GABA alone in enhancing neurochemical balance and lowering oxidative stress in a PPA-induced mouse model of autism, indicating promise for treating symptoms.